Pengaruh Influencer marketing dan Brand image Terhadap Keputusan Pembelian Produk Hand & Body Lotion: Studi pada Mahasiswa Manajemen Universitas Muhammadiyah Bandung Angkatan 2022 - Achmad Mansur Pauji; Halimah Zahrah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The Indonesian beauty industry has experienced rapid growth alongside increasing awareness of body care. Hand and body lotion has become a daily necessity among students, leading to intensified brand competition. Marina, as a local brand, faces challenges in maintaining its market position, as reflected in fluctuations in the Top Brand Index from 2021 to 2025. This study aims to analyze the effect of influencer marketing and brand image on purchasing decisions of Marina UV White hand and body lotion. A quantitative approach was employed using a survey method involving Management students of Universitas Muhammadiyah Bandung class of 2022, selected through purposive sampling. Data were analyzed using multiple linear regression. The results indicate that influencer marketing and brand image have a positive and significant effect, both partially and simultaneously, on purchasing decisions.